Effect of SILAR Cycles on the Thickness, Structural, Optical Properties of Cobalt Selenide Thin Films - N.J, Egwunyenga; V.C, Onuabuchi; N.L, Okoli; I.E, Nwankwo (International Research Journal of Multidisciplinary Technovation, 2021)
Cobalt Selenide thin films were fabricated using Successive Ionic Layer Adsorption and Reaction (SILAR) deposition technique at different SILAR cycles. The precursors for Cobalt and Selenium ions were CoCl2.6H2O and Na2SeSO3 respectively. Optical properties and thickness of the deposited films were studied to determine the effect of number of SILAR cycles on these properties. The optical absorbance of the films was found to decrease as wavelength increases and increases as SILAR cycle increases. Transmittance of the CoSe thin films was found to increase as the wavelength increases but decreases as number of SILAR cycles increased. The extinction coefficient of CoSe thin films decreases as wavelength increases but increases as the SILAR cycles increases. The energy band gap of CoSe thin films deposited decreases from 2.47 eV to 2.20 eV as number of SILAR cycles increases and film thickness increases from 92.96 nm and 225.63 nm. Structural properties of deposited cobalt selenide thin films showed that they correspond to orthorhombic phase of CoSe2 crystal structure of cobalt selenide thin films with crystallite size ranging from 7.63 nm to 13.07 nm.